A Mathematical Modelling for Workflows. (3rd November 2019) - Telles, Charles Roberto
Abstract : A mathematical heuristic model was proposed to analyze the flow of information in administrative workflows. The model starts from a conceptual analysis from the perspective of probabilistic systems, information theory, and information entropy. The main parameters of the analysis are to identify theoretically a workflow as a hybrid dynamic system where the probabilistic distribution of the information, the time of information processing, and the precision with which the workflow is executed are caused by the cognitive performance of agents within a complex adaptive system. The model of analysis provides support for the search for empirical evidence in workflow investigations, highlighting the presence or absence of agent ad hoc methods and their influence on firm's productivity.